Tipping the velvet - Waters, Sarah (Oberon Books, 2015)
It's 1887 and Nancy Astley sits in the audience at her local music hall: she doesn't know it yet, but the next act on the bill will change her life. Tonight is the night she'll fall in love' with the thrill of the stage and with Kitty Butler, a girl who wears trousers. Giddy with desire and hungry for experience, Nancy follows Kitty to London where unimaginable adventures await.
Keywords: 1800-1899; corps; europe; histoire et politique; identités LGBTQIA2+; personnes lesbiennes; périodes historiques; ressource en ligne; roman; royaume-uni; régions géographiques; sexualité; thématiques